Edukasi Pengetahuan Si Salam (Simpel Salam Untuk Hipertensi) Solusi Alami Rebusan Daun Salam Bagi Lansia Di Puskesmas Gadingrejo: Pengabdian - Yunita Anggriani; Nur Alfi Fauziah; Inggit Primadevi; Erna Wati; Mayang Widiyanti; Meta Andriyani; Nurjanah; Okta Mawarni; Riki Lutfhi Utari; Yeti Yulistyawati; Yuli Handayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aimed to improve the knowledge of elderly people regarding hypertension and the use of bay leaf decoction. The method applied was observational analytic with 21 elderly respondents suffering from hypertension at Gadingrejo Public Health Center on August 2, 2025. Data were collected using a questionnaire consisting of 15 questions administered before (pretest) and after (posttest) the health education. The education was delivered through leaflets and practical demonstrations on how to prepare bay leaf decoction. The results showed a significant improvement in participants’ knowledge scores. The average pretest score of 63.9 increased to 85 in the posttest, with a p-value of 0.000 (p<0.05). Almost all respondents experienced an increase in understanding, including those with initially low scores who demonstrated considerable improvement. In conclusion, health education on the use of bay leaf decoction was effective in improving the knowledge of elderly people with hypertension. It is recommended that the elderly utilize this therapy as a complement to medical treatment, with family support and guidance from health workers. Herbal therapy using bay leaves has the potential to be an affordable, easily accessible, and safe alternative for hypertension management in daily life.